2003
DOI: 10.1017/s095410200300110x
|View full text |Cite
|
Sign up to set email alerts
|

An optimum multiparameter mixing analysis of the shelf waters in the Ross Sea

Abstract: Abstract:The analysis of the mixing processes involving water masses on the Ross Sea continental shelf is one of the goals of the CLIMA project (Climatic Long-term Interactions for the Mass balance in Antarctica). This paper uses extended Optimum MultiParameter analysis (OMP), which is applied to four datasets collected during the cruises of 1994/95, 1995/96, 1997/98 and 2000/01 in the Ross Sea (Antarctica). Data include both hydrological, (temperature, salinity, and pressure; T, S, and P, respectively) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 48 publications
7
67
0
1
Order By: Relevance
“…The detailed description of the analysis is provided in several works (Mackas et al 1987, Tomczak & Large 1989, You & Tomczak 1993, and this kind of analysis has previously been used in the Ross Sea providing a good estimate of the mixing process and of the circulation of the different water masses (Budillon et al 2003).…”
Section: The MIX Methodsmentioning
confidence: 99%
“…The detailed description of the analysis is provided in several works (Mackas et al 1987, Tomczak & Large 1989, You & Tomczak 1993, and this kind of analysis has previously been used in the Ross Sea providing a good estimate of the mixing process and of the circulation of the different water masses (Budillon et al 2003).…”
Section: The MIX Methodsmentioning
confidence: 99%
“…The z * vertical coordinate can be used with a sea ice model (Campin et al, 2008) in NEMO (Madec and the NEMO team, 2016). However, modelling the ocean circulation within an ice shelf cavity in z * coordinates requires some modification of the existing code.…”
Section: Ocean Dynamicsmentioning
confidence: 99%
“…8). Weak winds in the atmospheric forcing , in addition to a fresher coastal current (Nakayama et al, 2014), the opening of a new pathway for HSSW circulation beneath the ice shelves (Budillon et al, 2003;Nicholls et al, 2009), mixing of HSSW with light surface waters all year long, and a deficiency of the seaice model in representing coastal polynyas could all help to explain the absence of HSSW in R_ISF.…”
Section: Sensitivity Of Ocean Properties To the Ice Shelf Cavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At 11°S, the error associated with the OMP is smaller than 2% in almost all the water column analyzed (Figure 63 At 27°S, the error is smaller than 1.5% for all models. According to Budillon et al (2003), Tomczak (1981), Tomczak & Large (1989), and Frants et al (2013), the mass balance constraint is used as a measure of the uncertainty of the result and mass balance residuals of 5% or less are considered acceptable. During the empirical tests to decide the best combination of weights for the OMP analysis, it was observed that if the importance of the potential vorticity was increased, the worse (be er) the results for the SACW (AAIW), i.e., bigger (smaller) mass balance constraints.…”
Section: South Atlantic Central Watermentioning
confidence: 99%